Analysis of Circular Elevatd Water Tank with Slant Columns Considering Hydrostatic Load - Sheikh Samroz; Hariram Sahu; Anudeep Nema (International Journal of Scientific Research in Civil Engineering, 2022)
Water tanks are the storage units of water which are used for distribution. Water tanks are constructed at high heads to distribute the water with the effect of gravity. These are mainly used for serving drinking water for highly populated areas of metropolitan urban communities in cities and towns. Water is the basic essential requirements for all living organisms in world. Frame works, transportation of inflammable fluids and chemicals. After tanks are used for water supply, firing. In this project work we are proposing circular elevated water tank considering slant height of 0o, 2o, 4o, 6o, 8o, 10o and 12o slope using analysis tool staad.pro. In this study we are considering hydraulic pressure as per I.S. 3370 L.S.M. and lateral forces.